Pengembangan Lembar Kerja Peserta Didik Berbasis Problem Based Learning Untuk Materi Matematika Kelas VIII - Zulfah; Fauzan, Ahmad; Armiati (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
This research was aimed at doing preliminary analysis in developing students’s worksheet based on problem solving. It uses Plomp’s model, consists of three phases. The first phase is analysis; need analysis, students analysis, curriculum analysis, concepts’ analysis and the existing teaching material’s analysis. It was found in the preliminary research that students’ worksheet that involve students’ critical thinking in the learning process is the teacher’s treatment to stimulate students’ skill in problem solving. Students’ work sheet problem based learning is the alternative to help the students to gain the students’ skill in problem solving.